Mandibular reconstructions using computer-aided design/computer-aided manufacturing: A systematic review of a defect-based reconstructive algorithm. Issue 9 (November 2015) - Tarsitano, Achille; Del Corso, Giacomo; Ciocca, Leonardo; Scotti, Roberto; Marchetti, Claudio
Abstract: Modern planning techniques, including computer-aided design/computer-aided manufacturing (CAD-CAM) can be used to plan reconstructive surgery, optimising aesthetic outcomes and functional rehabilitation. However, although many such applications are available, no systematic protocol yet describes the entire reconstructive procedure, which must include virtual planning, custom manufacture, and a reconstructive algorithm. We reviewed current practices in this novel field, analysed case series described in the literature, and developed a new, defect-based reconstructive algorithm. We also evaluated methods of mandibular reconstruction featuring virtual planning, the use of surgical guides, and laser printing of custom titanium bony plates to support composite free flaps, and evaluated their utility.